Q. 124.4( 15 Votes )

<span lang="EN-US

Answer :

1 – 2ab – (a2 + b2) = 1 – 2ab – a2 – b2


= 1 – (2ab + a2 + b2)


= 1 – (a + b)2


= (1 – a – b)(1 + a + b) a2 – b2 = (a – b)(a + b)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Factorize each ofRD Sharma - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Factorize each ofRD Sharma - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

10p2 +RS Aggarwal - Mathematics

7x2 - RS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics